Identification of the first enantiopure Rac1–Tiam1 protein–protein interaction inhibitor and its optimized synthesis via phosphine free remote group directed hydroarylation. Issue 2 (17th January 2019) - Ruffoni, Alessandro; Ferri, Nicola; Pinto, Andrea; Pellegrino, Sara; Contini, Alessandro; Clerici, Francesca
Abstract : The remote substituent regiocontrol of phosphine free Heck hydroarylation has been exploited for the preparation of the first enantiopure inhibitor of Rac1–Tiam1 PPI. Abstract : A phospine free hydroarylation reaction applied to norbornene derivatives is described for the first time and was exploited for the regioselective gram scale synthesis ofAR-148, a known Rac1–Tiam1 PPI inhibitor. Umpolung conversion of the nitro group into free amine allowed the regiocontrol of the key arylation step via a long range effect. The effect ofAR-148 in comparison with its enantiomers on Rac1 activation of has been evaluated and (−)AR-148 has been identified as the first enantiomerically pure inhibitor of Rac1–Tiam1 PPI.